Evaluation of social work supervision on job performance in the department of social development, Polokwane Sub-District : implications for practice - Manthosi, Frans Lesetja (University of Limpopo, 2016)
The overall aim of the study was to evaluate how Social Work Supervision affects job performance in the Department of Social Development, Polokwane Sub-District. The objectives of the study were to explore how supervision is rendered in the Department of Social Development in the Polokwane sub-district; to investigate the impact of supervision on Social Workers’ job performance and to make recommendations from the findings to the Department of Social Development in the Polokwane sub-district regarding how supervision can be improved to enhance service delivery. The study was qualitative research and researcher used descriptive research design. The data was collected through semi-structured face-to-face interview from six (6) cluster supervisors and twelve (12) Social Workers who are employed by the Department of Social Development, Polokwane Sub-District. The sample consisted of cluster supervisors who had more than three months experience of providing supervision in the Department of Social Development, Polokwane Sub-District and no acting cluster supervisor was selected to participate in the study. The Social Workers had more than three months of working experience at Department of Social Development, Polokwane Sub-District. These Social Workers were not on internship programme. The researcher used thematic data analysis. The findings of this study confirmed that supervision which is rendered in the Department of Social Development, Polokwane Sub-District is conducted by supervisors who did not receive training during their academic years and after being qualified Social Workers; supervisors conduct this critical role because of their years of experience as Social Workers. Secondly Supervision sessions which are conducted by effective supervisors who have good supervisory skills have a positive impact on the job performance of Social Workers, as compare to ineffective supervisors without good supervisory skills and thirdly none adherence to structured supervision under poor working conditions without resources with high caseloads and unfair remuneration leads to burnout, and consequently contributing towards Social Workers having the intention to leave the Department of Social Development. Key words: Cluster supervisors, Social Workers, Job performance and supervision
Thesis (M.A. (Social Work)) --University of Limpopo, 2016
Keywords: Cluster supervisors; Social workers; Job performance; Supervision; Employees rating of; Supervision -- Employees rating of